2010
DOI: 10.5210/fm.v15i12.2745
|View full text |Cite
|
Sign up to set email alerts
|

Twitter content classification

Abstract: This paper delivers a new Twitter content classification framework based sixteen existing Twitter studies and a grounded theory analysis of a personal Twitter history. It expands the existing understanding of Twitter as a multifunction tool for personal, profession, commercial and phatic communications with a split level classification scheme that offers broad categorization and specific sub categories for deeper insight into the real world application of the service.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
99
0
7

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(109 citation statements)
references
References 0 publications
3
99
0
7
Order By: Relevance
“…Yet social penetration theory (Altman & Taylor, 1973) and theories of social exchange (Homans, 1958;Thibaut & Kelly, 1959) suggest that superficial disclosures may have important consequences in personal relationships. Moreover, scholars have noted the potential of new communication technologies for sharing trivial content (Miller, 2008;Tong & Walther, 2011), and recent content analyses have demonstrated that superficial information is routinely disclosed using several different technologies (Dann, 2010;Lee, 2011;Oulasvirta, Lehtonen, Kurvinen, & Raento, 2010;Rettie, 2009). This study attempts to better understand the implications of superficial disclosure in personal relationships by examining the outcomes associated with receiving superficial self-disclosures from friends via five communication technologies.…”
mentioning
confidence: 99%
“…Yet social penetration theory (Altman & Taylor, 1973) and theories of social exchange (Homans, 1958;Thibaut & Kelly, 1959) suggest that superficial disclosures may have important consequences in personal relationships. Moreover, scholars have noted the potential of new communication technologies for sharing trivial content (Miller, 2008;Tong & Walther, 2011), and recent content analyses have demonstrated that superficial information is routinely disclosed using several different technologies (Dann, 2010;Lee, 2011;Oulasvirta, Lehtonen, Kurvinen, & Raento, 2010;Rettie, 2009). This study attempts to better understand the implications of superficial disclosure in personal relationships by examining the outcomes associated with receiving superficial self-disclosures from friends via five communication technologies.…”
mentioning
confidence: 99%
“…Enhancements to the algorithms and reclassification of the entire database were conducted as needed. The development of the fitness tweet classification model was based on available macro topic classification models where tweets were categories into broad categories of content, based on prior literature [18], and sourced from other works [8,11,13,19]. These prior literatures indicated four major categories for sharing on Twitter-Conversational, Pass-Along, News, and Status-categories that are consistent with Java's [11] research on the primary purposes of tweets.…”
Section: Original Researchmentioning
confidence: 86%
“…The size of Twitter's user community (at time of writing it has 313 million active users (Twitter 2016), more than double that of Tumblr (Flynn 2016)) has meant much published microblogging research is focussed on it: Williams et al (2013) identified over 1000 papers published by the close of 2011. Classifications of research approaches to Twitter have emerged which can help the community situate future work (Cormode et al 2010, Dann 2010, Cheong and Ray 2011, Barnes and Bohringer 2011, Williams et al 2013 Despite the significant size of its online communities (Tumblr 2016b, see also Anderson (2015, p. 161) is only able to identify two "scholarly resources" , Chang et al 2014, when as our findings will show, there were actually many more in circulation at the time of writing. Hillman et al (2014b) claim "We also found that nobody has studied Tumblr fandoms before", when other research was published on Tumblr fandoms devoted to film ) and television (Booth 2013) iii .…”
Section: Literature Reviewmentioning
confidence: 71%